Adsorption of Lead Ion (II) Using Activated Carbon of Langsat Shell (Lansium domesticum Corr) with Column Method - Muhammad Taufiq; Desy Kurniawati (Universitas Negeri Medan, 2023)
Lead (II) ion is one of the dangerous metal ions produced from various industrial wastes and its existence needs to be addressed. Adsorption using langsat peel activated carbon was proven to be able to absorb lead (II) ions. The stages of absorption are carried out by varying the adsorbent weight (0.2, 0.3, 0.4, and 0.5) g, and flow rate (1,2,3,4) mL/minute by column method then continued with testing using atomic absorption spectrophotometer (AAS). The results showed that the optimum conditions occurred at the weight of the adsorbent is 0.2 g, and the flow rate is 2 mL/min.